A Review: Ophiocordycep Sinensis (Berk.) as a Traditional Tibetan Medicine and its Potential in the Treatment of Various Human Ailments - Kom, Yangchen D.; Karthiyayini, R. (Current Traditional Medicine, 2024)
Nature’s never-ending gift, which counts as one of the most valuable medicines in the entire world, the Ophiocordyceps sinensis, also known as caterpillar fungus, is a traditional Chinese medicine found in Tibetan plateaus. During the season of spring, many shepherd search for this caterpillar fungus as its value in the market is very high. Moreover, due to the effects of climatic change on its population and increasing demand, O. sinensis is now an endangered species. It can treat almost many diseases, such as cardiovascular disease, respiratory diseases, immune dysfunction etc. The chemical composition of this fungus includes amino acids, glutamic acid, polyamines, cordycepic acid, saccharides, sterols, nucleotides, sugar derivatives, fatty acids, vitamins, and oleic acid.
Keywords: immune dysfunction